Foamy macrophages in the liver of cattle fed Brachiaria brizantha hay - Torres, Márcia Bersane Araújo de Medeiros; Coelho, Kunie Iabuki Rabello [UNESP] (My University, 2003)
Liver and lymph nodes injuries characterized by clusters of foamy macrophages, some of them containing birefringent crystals, were observed in cattle fed on Brachiaria brizantha hay. The cattle were from an experimental group poisoned with Senecio brasiliensis known to cause hepatic fibrosis and hepatocyte megalocytosis. One of the animals developed photosensitivity but the exact cause wasn't determined since both plants were fed. The foamy macrophages were present from the 30th d of feeding. Early appearance of these lesions may be particular to the animal specie used or due to the presence of both toxic plants.
Keywords: liver enzyme; animal experiment; animal tissue; Brachiaria brizantha; controlled study; foamy macrophage; hay; histopathology; liver; liver cell; liver fibrosis; macrophage; megalocytosis; nonhuman; photosensitivity; Senecio; Animals; Brachiaria; Cattle; Cattle Diseases; Foam Cells; Hepatitis, Toxic; Liver; Macrophages; Plant Poisoning; Animalia; Bos taurus; Senecio brasiliensis; Urochloa brizantha; Vertebrata